2005
DOI: 10.1142/s0217751x05023578
|View full text |Cite
|
Sign up to set email alerts
|

HEAVY QUARKONIUM π+π- TRANSITIONS AND A POSSIBLE $b\bar{b}q\bar{q}$ STATE

Abstract: π + π − transitions of heavy quarkonia, especially the Υ(3S) → Υ(1S)π + π − decay process, are revisited. In the framework of the Chiral Unitary Theory (ChUT), the S wave ππ final state interaction (FSI) is included. It is found that when an additional intermediate state with J P = 1 + and I = 1 is introduced, not only the ππ invariant mass spectrum and the cosθ * π distribution in the Υ(3S) → Υ(1S)π + π − process can simultaneously be well-explained, but also a consistent description for other bottomonia π + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…Lewis acids are also efficient catalysts for aromatic H−D exchange. Guo et al [67] . used Lewis acids, such as MoCl 5 , WCl 6 , NbCl 5 , and TaCl 5 , to achieve complete exchange of all hydrogen atoms on aromatic rings with C 6 D 6 as the deuterium source.…”
Section: H−d Exchangementioning
confidence: 99%
See 1 more Smart Citation
“…Lewis acids are also efficient catalysts for aromatic H−D exchange. Guo et al [67] . used Lewis acids, such as MoCl 5 , WCl 6 , NbCl 5 , and TaCl 5 , to achieve complete exchange of all hydrogen atoms on aromatic rings with C 6 D 6 as the deuterium source.…”
Section: H−d Exchangementioning
confidence: 99%
“…Lewis acids are also efficient catalysts for aromatic HÀ D exchange. Guo et al [67] used Lewis acids, such as MoCl 5 , WCl 6 , NbCl 5 , and TaCl 5 , to achieve complete exchange of all hydrogen atoms on aromatic rings with C 6 D 6 as the deuterium source. Chang et al [68] found that regioselective deuterium labeling of the β-amino CÀ H bonds in N-alkylamine-based pharmaceutical compounds could be achieved using the B(C 6 F 5 ) 3 catalytic system.…”
Section: Acid/base Catalystsmentioning
confidence: 99%
“…An alternative fit shown in Fig. 51(b) describes the VPP vertex using an effective Lagrangian and includes universal ππ S-wave rescattering in the final state [440], thus overcoming the violation of unitarity by naïvely employing contact term and f 0 (500) resonance (as an approximation to rescattering effects) additively. Here, the f 0 (500)-pole parameters are taken from Ref.…”
Section: M(ηπ) [Gev]mentioning
confidence: 99%
“…The coherent sum of the contributions describes the data well. Panel (b) shows the invariant mass fitted by the chiral unitarity approach [440]. Dots with error bars are data, and the histograms are the fit results.…”
Section: M(ππ) [Gev]mentioning
confidence: 99%